A SET ASPECT OF PAPER MONEY: A Reading on Ahmad Khatib Al-Minangkabawi's Thought - Sholihin, Muhammad (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
This article aims to identify Sheikh Ahmad Khatib Al-Minangkabauwi's initial concept of Paper Money, which in the early 19th century wrote Raf'ul Iltibas. Through a qualitative approach, with critical extraction analysis, several things can be revealed related to the thoughts of Sheikh Ahmad Khatib Al-Minangkabauwi about paper money. From a careful reading of Sheikh Ahmad Khatib Al-Minangkabauwi, several significant findings can be formulated: First, in his work, Ahmad Khatib Al-Minangkabauwi applies two methods lead to his critical thinking about Paper money, namely the comparative law method and Qiyas. Second, Sheikh Ahmad Khatib believes that paper money has similarities with dinars and dirhams in several aspects, namely the function of its nominal value. It is just that the existence of these values is different. The value of paper money is politico-economic. Meanwhile, the nominal value of dirhams and dinars is intrinsic and natural. Sheikh Ahmad Khatib Al-Minangkabau's work related to Paper Money is written heavily from the perspective of fiqh. Briefly, it is challenging to describe economic assumptions from work. As a result, articles are also thicker with fiqh analysis. Sheikh Ahmad Khatib Al-Minangkabauwi's view regarding Paper Money becomes the foundation for the theory of the value of money in Islam. However, it is rarely disclosed, so that this paper can serve as the foundation of the value for money offered by scholars from Indonesia in the early 19th century. Strengthening the idea that money is not suitable as a commodity must be positioned as capital to be productive and finally becomes why trade is compelling and becomes the most practical reason for removing Zakat from it. There are not many, not even articles that attempt to reveal the concept of classical ulama from Indonesia relating to Paper Money. This article manages to identify that, and at the same time, becomes a novelty.